2018
DOI: 10.1002/anie.201811343
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Synthesis of ortho‐Substituted 1,1‐Diarylalkanes by a 1,2‐Metalate Rearrangement/anti‐SN2′ Elimination/Rearomatizing Allylic Suzuki–Miyaura Reaction Sequence

Abstract: The one‐pot sequential coupling of benzylamines, boronic esters, and aryl iodides has been investigated. In the presence of an N‐activator, the boronate complex formed from an ortho ‐lithiated benzylamine and a boronic ester undergoes stereospecific 1,2‐metalate rearrangement/anti‐S N 2′ elimination to form a dearomatized tertiary boronic ester. Treatment with an aryl iodide under palladium catalysis leads to rearomatizing γ‐selective allylic Suzuki–Miyaura cross‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Enantioenriched 1,1-diaryl alkanes are a key skeleton in a series of natural products and bio-active molecules, such as sertraline 1 , tolterodine 2,3 , podophyllotoxins 4 , etc 58 . Due to the broad application of 1,1-diaryl alkanes in pharmaceutical industry, their asymmetric synthesis has attracted intensive interests in organic chemistry community and multiple strategies have been developed 917 . As a highly efficient and direct methodology for generating stereogenic centers in target molecules, transition-metal-catalyzed enantioselective cross-coupling reactions of electrophiles with organometallic reagents have been developed by Fu and colleagues 18 , and Molander and colleagues 19,20 to furnish 1,1-diaryl alkanes using chiral bioxazolines (BiOX) as ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Enantioenriched 1,1-diaryl alkanes are a key skeleton in a series of natural products and bio-active molecules, such as sertraline 1 , tolterodine 2,3 , podophyllotoxins 4 , etc 58 . Due to the broad application of 1,1-diaryl alkanes in pharmaceutical industry, their asymmetric synthesis has attracted intensive interests in organic chemistry community and multiple strategies have been developed 917 . As a highly efficient and direct methodology for generating stereogenic centers in target molecules, transition-metal-catalyzed enantioselective cross-coupling reactions of electrophiles with organometallic reagents have been developed by Fu and colleagues 18 , and Molander and colleagues 19,20 to furnish 1,1-diaryl alkanes using chiral bioxazolines (BiOX) as ligands.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that this key enantioenriched dearomatized intermediate can participate in allylboration and allylic Suzuki-Miyaura cross-coupling reactions to provide complex enantioenriched products [Scheme 1(B)]. 5,6 Importantly, all of these transformations use rearomatization as a driving forcing. We were, however, interested in diverting reactivity along an alternative pathway, avoiding rearomatization and thereby retaining valuable functionality.…”
mentioning
confidence: 99%
“…Further work highlighted the synthetic utility of the intermediate enantioenriched dearomatized tertiary boronic esters 113,w hich were utilized in rearomatizing allylic Suzuki-Miyaura cross-coupling reactions to provide complex enantioenriched 1,1-diarylmethane products 116 with three readily addressable points of diversification (Scheme 20 c). [49] In an alternative N-acylation-induced 1,2-migration of aryl boronate complexes,A ggarwal developed ag eneral protocol for the stereospecific coupling of chiral secondary and tertiary boronic esters with electron-deficient N-heteroaromatics (Scheme 21 a). [50] After formation of chiral boronate complexes 119 from lithiated 6-membered ring Nheterocycles 117 (including pyridines,q uinolines and isoquinolines), 1,2-migration was triggered by N-acylation with 2,2,2-trichloroethyl chloroformate (Troc-Cl), leading to dearomatized tertiary boronic ester 121 via the intermediate Nacyl pyridinium 120.Aone-pot oxidation/hydrolysis/elimination sequence finally furnished the coupled heteroaromatic products 118 with complete stereospecificity.Amodified approach was reported by Ready,i nw hich the pyridyl boronate complexes 119 were generated by adding organometallic reagents to 4-pyridyl boronic ester 18 e (Scheme 21 b).…”
Section: Minireviewsmentioning
confidence: 99%